2014
DOI: 10.3892/or.2014.3578
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of PLZF in human hepatocellular carcinoma and its clinical significance

Abstract: Abstract. Promyelocytic leukemia zinc finger (PLZF) acts as a tumor-suppressor gene in a series of cancers including prostate, melanoma, colon cancer and leukemia. However, its role in hepatocellular carcinoma (HCC) has not yet been illustrated. The present study aimed to investigate the expression and epigenetic regulation of PLZF as well as its clinical significance in HCC. We found that the expression of PLZF was significantly downregulated in HCC samples at both the RNA level (P<0.001) and protein level c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
(13 reference statements)
2
8
0
Order By: Relevance
“…PCOLCE (Procollagen C-Endopeptidase Enhancer) has been shown to be the strongest in its correlation with the liver fibrosis phenotype (Ippolito et al, 2016). ZBTB16, also named as PLZF, has previously been shown to be down-regulated in hepatocellular carcinoma, which supports our current study that ZBTB16 was down-regulated in liver cancer specimens compared to non-tumor liver specimens (Hui et al, 2015). PIN1 has been shown to contribute to hepatic carcinogenesis (Pang et al, 2006), while targeting PIN1 has been suggested to be a promising therapeutic approach for hepatocellular carcinoma .…”
Section: Discussionsupporting
confidence: 91%
“…PCOLCE (Procollagen C-Endopeptidase Enhancer) has been shown to be the strongest in its correlation with the liver fibrosis phenotype (Ippolito et al, 2016). ZBTB16, also named as PLZF, has previously been shown to be down-regulated in hepatocellular carcinoma, which supports our current study that ZBTB16 was down-regulated in liver cancer specimens compared to non-tumor liver specimens (Hui et al, 2015). PIN1 has been shown to contribute to hepatic carcinogenesis (Pang et al, 2006), while targeting PIN1 has been suggested to be a promising therapeutic approach for hepatocellular carcinoma .…”
Section: Discussionsupporting
confidence: 91%
“…3). These effects were similar to observations in lung cancer, melanoma, prostate cancer and hepatocellular carcinoma (7,8,34,35).…”
Section: Discussionsupporting
confidence: 88%
“…Except for hematological malignancies, PLZF has also been implicated in various solid tumors. The loss of PLZF expression in tumors compared with normal tissue has been observed in melanoma, hepatocellular carcinoma, pancreatic and lung cancer, thyroid carcinoma, prostate and gallbladder cancer (5)(6)(7)(8)(9)(10)(11), and increased PLZF expression in tumors has been observed in clear cell renal cell carcinoma, colon cancer, glioblastoma and testicular seminoma (3,12). However, the expression and value of PLZF in gastric cancer (GC) have not been studied, and it is reasonable to think that PLZF may play an important role in GC.…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, the expression of PLZF was dramatically downregulated in hepatocellular carcinoma samples at both the RNA and protein levels in comparison to those of adjacent normal tissues. 25 Besides, PLZF expression was found to be substantially lower in high-risk melanomas than that in low-risk melanomas. 26 Although PLZF has emerged as an promising functional component during CRC progression, the underlying mechanism of tumorigenesis mediated by PLZF is not fully understood.…”
Section: Discussionmentioning
confidence: 95%